Learning games creation: IMIE model - Ali Abarkan; Abderrahim Saaidi; Majid Ben Yakhlef (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this article, we propose a new model for the learning games design, which aims to enrich and solve the problems of existing models. From the work carried out around the models of educational games, we carefully identify a series of steps to follow, taking into account the simplicity, ease of adaptation and the integration of several factors interest such as the integration of a set sub-models treated pedagogically define the pedagogical side in the game, also the distribution of the intervening necessary for each of the stages to ensure better collaboration between them, for the purpose to helping the creators to trace their path from the start of the creation, in order to achieve the best example of games with an adequate oscillation pedagogical-fun, that will meet the requirements of existing classical teaching methods.